Quantum Non-Markovian Environment-to-System Backflows of Information: Nonoperational vs. Operational Approaches - Budini, Adrian Adolfo (Molecular Diversity Preservation International, 2022)
Fil: Budini, Adrian Adolfo. Universidad Tecnológica Nacional; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina